WOMEN AND CAREER IN THE QUR’AN: A COMPARATIVE STUDY OF INTERPRETATIONS BY FEMALE MUFASSIRUN (BADRIYAH FAYUMI, NAILAH HASYIM SABRI, AND AISYAH ABDURRAHMAN) - Muhajjalin, Ghurratul; Fawaid, Ahmad (Program Pascasarjana UIN Sumatera Utara, 2025)
The concept of career women in the perspective of the Qur'an has become increasingly relevant in response to social dynamics and the challenges of modernity, where women are playing a more active role in the public sphere. The study of interpretations by female mufassirun, such as Badriyah Fayumi, Nailah Hasyim Sabri, and Aisyah Abdurrahman (Bintu Syathi’), is essential to understand how the Qur'an can be interpreted in a contemporary context, particularly regarding women's rights and responsibilities. The presence of female mufassirun offers a distinctive perspective that is often overlooked in the male-dominated tafsir tradition. Badriyah Fayumi focuses on a contextual understanding of the Qur’anic verses related to women, while Nailah Hasyim Sabri proposes a more inclusive approach. Aisyah Abdurrahman emphasizes that women possess intellectual capacity and actively contribute to public life, as reflected in her struggle for access to education and academic positions. This research demonstrates that female mufassirun provide space for women to actively engage in careers. The Qur'an acknowledges women’s involvement in various productive activities, as long as they adhere to the principles of Shari'ah. The interpretations developed by female mufassirun emphasize gender equality, justice, and women’s rights to contribute to social and economic life. The feminist approach advocated by Badriyah Fayumi reconstructs the patriarchal classical tafsir by highlighting values of equality, justice, and consultation in gender relations.